Ethical and Legal Dilemmas in the Age of a Global Pandemic - A. B. Didikin; D. G. Trinitka (Теоретическая и прикладная юриспруденция)
The paper is devoted to the analysis of current trends in the formation of ethical and legal dilemmas in society under the inﬂuence of a global pandemic. Based on the consideration of the key arguments characterizing the dominant forms of legal discourse in the modern philosophy of law, the authors justify a number of contradictions that lead to realistic ideas about law and the possibility of direct use in the practice of law enforcement of these empirical sciences. The key social problems and challenges that have developed under the inﬂuence of the pandemic are considered, as well as the possibilities of overcoming contradictions between the values of citizens, the need to ensure legal principles and restore an effective dialogue between the authorities and society when applying emergency measures.